2011
DOI: 10.1093/qjmed/hcr209
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning and the older patient

Abstract: Making treatment decisions for older people is difficult, because of the complex interplay of their multiple co-morbidities, but also because of the fine balance of risks vs. benefit in any chosen management plan. This becomes even more difficult when they lose the capacity to tell us what they want, and often in such situations we have to rely on information from others in order to make decisions based on their best interests. Advance care planning should help with making these decisions clearer, based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…For example, since the adoption of the Patient SelfDetermination Act in the USA in 1991, only 10% of patients have prepared AD (18). Similar rates of uptake have been reported in Germany (19), the Netherlands (20), and the United Kingdom (21). Rates are reportedly even lower in Australia, at 0.2% to 7.9% (22) and Spain (<1%) (23).…”
Section: What Exactly Are Acp and Ad?supporting
confidence: 79%
“…For example, since the adoption of the Patient SelfDetermination Act in the USA in 1991, only 10% of patients have prepared AD (18). Similar rates of uptake have been reported in Germany (19), the Netherlands (20), and the United Kingdom (21). Rates are reportedly even lower in Australia, at 0.2% to 7.9% (22) and Spain (<1%) (23).…”
Section: What Exactly Are Acp and Ad?supporting
confidence: 79%
“…In our cross‐sectional analysis undertaken over a 3‐day period, none of the 100 patients aged 80 years or above admitted to an acute hospital in Sydney had ACD available in their medical records. These data give further evidence of the infrequency of ACD among elderly hospitalised Australians despite policies and literature outlining the importance of such documents . The reason for this may be a low frequency of ACD completion by elderly people in the community, as well as a failure of pre‐existing ACD making their way into the medical record for hospitalised patients .…”
Section: Discussionmentioning
confidence: 88%
“…36 Some studies have explored levels of agreement between people with long-term illness and their family carers and indicate varying levels of concordance. 37 In a qualitative study of dyads involving heart failure, Retrum et al 38 found that lack of agreement could impair the ACP process.…”
Section: Discussionmentioning
confidence: 99%